Enhancement and explosion-proof mechanism of aluminum fiber addition in Al2O3–SiC–C castables for iron runner. Issue 17 (1st December 2019) - Li, Yichong; Zhao, Huizhong; Zhang, Han; Pan, Dunxiang; Feng, Yunkang; Li, Yuangao; Wang, Xinquan; Guo, Yindong
Abstract: As a certain amount of water is typically discharged during the baking of castables, explosion of castables remains an issue. The explosion-proof performance and mechanical strength of castables are attracting increasing attention. In this study, the formation model of dense alumina-metal aluminum composite layer was established and an explosion-proof mechanism of aluminum fiber addition was proposed in this paper. The effect of aluminum fiber addition (0.5, 1, 2, and 3 wt%) on mechanical strength and burst resistance of Al2 O3 –SiC–C (ASC)-based castables for iron runner was studied. The results showed that the addition of metal aluminum fiber could effectively improve burst resistance, volume stability and mechanical strength of ASC castables. The castables had better strength when 0.10–0.20 wt% aluminum fiber was added. Closed pores with dense alumina layers and tiny exhaust channels relieved the stress, improving the mechanical strength of the castables. When the aluminum fiber content exceeded 0.20 wt%, the strength of the castables decreased because of the formation of interconnected pores. When 0.20 wt% aluminum fiber was added, the sample showed the best overall performance by forming pores with a dense layer of alumina.